Nitrogen regulation by natural systems in "unnatural" landscapes: denitrification in ultra-urban coastal ecosystems. Issue 9 (2nd September 2018) - Rosenzweig, Bernice R.; Groffman, Peter M.; Zarnoch, Chester B.; Branco, Brett F.; Hartig, Ellen K.; Fitzpatrick, James; Forgione, Helen M.; Parris, Adam
ABSTRACT: Dense cities represent biogeochemical hot spots along the shoreline, concentrating fixed nitrogen that is subsequently discharged into adjacent coastal receiving waters. Thus, the ecosystem services provided by natural systems in highly urban environments can play a particularly important role in the global nitrogen cycle. In this paper, we review the recent literature on nitrogen regulation by temperate coastal ecosystems, with a focus on how the distinct physical and biogeochemical features of the urban landscape can affect the provision of this ecosystem service. We use Jamaica Bay, an ultra-urbanized coastal lagoon in the United States of America, as a demonstrative case study. Based on simple areal and tidal-based calculations, the natural systems of Jamaica Bay remove ~ 24% of the reactive nitrogen discharged by wastewater treatment plants. However, this estimate does not represent the dynamic nature of urban nitrogen cycling represented in the recent literature and highlights key research needs and opportunities. Our review reveals that ecosystem-facilitated denitrification may be significant in even the most densely urbanized coastal landscapes, but critical uncertainties currently limit incorporation of this ecosystem service in environmental management.